The Scope of Discretion in Government Administration Law: Constitutional or Unconstitutional? - Victor Imanuel W. Nalle (Faculty of Law, Hasanuddin University, 2018)
Law No. 30 of 2014 on Government Administration (Government Administration Law) has set the scope of discretion in Indonesian legal system. But the form of discretion is limited in scope government decision (KTUN) and factual actions of the government. The restriction implicates circulars or others policy rule is not a form of discretion. In addition, the provisions concerning the terms of use discretion, procedures and legal effect of discretion in the Government Administration Law are not applicable to the use of policy rule. In fact, the substance of discretion in policy rule (e.g. circulars and instructions) has the potential of conflicting laws and regulations and/or General Principles of Good Administration. The legal issues in this study are the constitutionality of the scope of discretion in Article 1 point 9 and Article 23 paragraph (1) of the Government Administration Law. This analysis showed that limits the scope of discretion in Government Administration Law contrary to formal elements, substantive, and control mechanisms within the rule of law. This analysis also suggests the expansion of the scope of discretion in the Government Administration Law and setting policy rules as the object of the petition for judicial review so that there is a control mechanism by trial to discretion in the form of policy rule.